Relationship between Socioeconomic Factors and the Incidence of Stunting In Padang Jaya Village, Bengkulu Utara Regency - Melya Ariana; Lela Rospida (UNIVED Press, 2024)
Stunting is a condition in which a young child has impaired growth due to chronic spikes in nutrition, making him or her weaker than other children of the same age. Globally, stunting is a more serious problem than wasting and underweight. A number of factors, including socioeconomic factors stemming from wages, education, and awareness of the impact of stunting. The purpose of this study is to understand the social and economic consequences of stunting in Padang Jaya Village, North Bengkulu Regency. This research uses Quantitative methods by using a systematic, organized, and continuous process from the beginning to the end of the research.